PERBANDINGAN PENGARUH PENGGUNAAN ZAT PENGATUR TUMBUH EKSTRAK BAWANG BOMBAY MERAH (Allium cepa L.) DAN BAWANG MERAH (Allium ascalonicum L.) TERHADAP PERTUMBUHAN TANAMAN SELADA (Lactuca Sativa.) - Waskito, Rusyariyanto; Anggarani, Mirwa Adiprahara (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2024)
Vegetables are a food ingredient that has an important role in the body. This causes increasing consumer demand for vegetables, especially organic vegetables. To meet consumer needs for organic vegetables, innovation in cultivation is needed, one of which is the use of Growth Regulators (GRS). Natural ingredients that can be used as GRS are shallots and red onions. This research aims to identify the effect of using ZPT from the allium genus on lettuce cultivation. Phytohormones can have a major influence on cell division and root elongation and stimulate the growth of leaves and stems. This research was carried out on lettuce plants using a Randomized Block Design (RBD) with 7 treatments and 6 repetitions. The parameters used in this research include plant height, leaf circumference, number of leaves, and plant wet biomass. The results of the study showed that GRS from shallots with a concentration of 45% gave the highest yields on lettuce plants with the parameters of plant height, number of leaves, leaf circumference, and wet biomass respectively, namely 20,75 cm, 20 leaves, 34 cm and 20,33 grams